Efficient Detection of Phishing Websites Using Multilayer Perceptron - Odeh, Ammar Jamil; Keshta, Ismail; Abdelfattah, Eman (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Phishing is a type of Internet fraud that aims to acquire the credential of users via scamming websites. In this paper, a novel approach is utilized that uses a Neural Network with a multilayer perceptron to detect the scam URL. The proposed system improves the accuracy of the scam detection system as it achieves a high accuracy percentage of 98.5%.